Inoculation with Micromonospora sp. enhances carbohydrate and amino acid production, strengthening antioxidant metabolism to mitigate heat stress in wheat cultivars - Hassan, Abdelrahim H. A.; Ahmed, Enas Shaban; Sheteiwy, Mohamed S.; Alhaj Hamoud, Yousef; Okla, Mohammad K.; AlGarawi, Amal Mohamed; Maridueña-Zavala, Maria Gabriela; Alaraidh, Ibrahim A.; Reyad, Ahmed M.; Abdelgawad, Hamada (Frontiers in Plant Science, 2024)
This research investigated the biochemical, physiological, and antioxidant responses of wheat plants under heat stress, focusing on the role of plant growth-promoting bacteria (Micromonospora sp.). Two wheat genotypes were studied: one heat-sensitive and one heat-tolerant, examining their responses to heat stress with and without bacterial inoculation. Under heat stress, the sensitive cultivar experienced significant reductions in photosynthesis rate, chlorophyll content, and RuBisCO activity (–57-61%), while the tolerant cultivar had milder reductions (–24-28%). Micromonospora sp. treatment notably improved these parameters in the sensitive cultivar (+48-78%), resulting in a substantial increase in biomass production (+43-53%), which was not seen in the tolerant cultivar. Additionally, oxidative stress markers (H2O2 and MDA) were elevated more in the sensitive cultivar (82% and 90% higher) compared to the tolerant one. Micromonospora sp. treatment effectively reduced these markers in the sensitive cultivar (-28% and -27%). Enhanced activity of antioxidant enzymes and ASC-GSH pathway enzymes was particularly evident in Micromonospora sp.-treated sensitive plants. Carbohydrate metabolism shifted, with increased soluble sugars and significant rises in sucrose content in Micromonospora sp.-treated plants under stress. The higher soluble sugar levels facilitated amino acid synthesis, contributing to biosynthesis of secondary metabolites, including flavonoids, polyphenols, and anthocyanins. This was reflected in increased activity of phenylalanine ammonia-lyase, cinnamate (CA) 4-hydroxylase, and chalcone synthase enzymes, indicating the activation of phenylpropanoid pathways. Overall, the findings suggest that Micromonospora sp. can mitigate heat stress effects by enhancing photosynthetic efficiency, antioxidant defense, and metabolic adaptations in heat-sensitive wheat cultivars.